Study of Physico-Chemical Characteristics of Surface Water Using Regression Analysis of Cauvery River and Its Tributaries in Tamilnadu, India - Hema, S.; Subramani, T. (Asian Journal of Chemistry, 2013)
Cauvery river is one of the important rivers of peninsular India. Because of its importance in culture and dense population along its banks, it is facing a lot of anthropogenic influences. In this study, surface water samples were collected from 50 stations in the river and its tributaries and analyzed for its physicochemical characteristics in February 2009 and October 2009 in order to understand the sources of water pollution and the evolution of water quality. The results indicate a significant variation among the water quality parameters in the river which was also influenced by the quality of water from its tributaries. Seasonal variations were observed in the river, which was due to catchment characteristics and point or nonpoint sources of pollution. Pearson correlation used to determine the correlation between the water quality parameters was found to be highly correlated. The regression equations developed to estimate the parameters responsible for water quality variations are found to be useful for assessment of missing data in order to get better information about the quality of surface water.